Induction of apoptosis by pistachio (Pistacia vera L.) hull extract and its molecular mechanisms of action in human hepatoma cell line HepG2 - Fathalizadeh, J; Bagheri, V; Khorramdelazad, H; Kazemi Arababadi, M; Jafarzadeh, A; Mirzaei, M R; Shamsizadeh, A; Hajizadeh, M R (Cellular and Molecular Biology, 2015)
Several important Pistacia species such as P. vera have been traditionally used for treating a wide range of diseases (for instance, liver-related disorders). There is a relative lack of research into pharmacological aspects of pistachio hull. Hence, this study was aimed at investigating whether pistachio rosy hull (PRH) extract exerts apoptotic impacts on HepG2 liver cancer cell line. In order to evaluate cell viability and apoptosis in response to treatment with the extract, MTT assay and Annexin-V-fluorescein/propidium iodide (PI) double staining were performed, respectively. Moreover, molecular mechanism of apoptosis induced by the extract was determined using human apoptosis PCR array. Our findings showed that PRH extract treatment reduced cell viability (IC50 0.3 mg/ml) in a dose-dependent manner. Flow cytometric analysis revealed that the extract significantly induced apoptosis in HepG2 cells. In addition, quantitative PCR array results demonstrated the regulation of a considerable number of apoptosis-related genes belonging to the TNF, BCL2, IAP, TRAF, and caspase families. We observed altered expression of both pro-apoptotic and anti-apoptotic genes associated with the extrinsic and intrinsic apoptosis signaling pathways. These results suggest that the aqueous extract of PRH possesses apoptotic activity through cytotoxic and apoptosis-inducing effects on HepG2 cells.